Ozone-Induced Programmed Cell Death in the Arabidopsis radical-induced cell death1 Mutant - Overmyer, Kirk (American Society of Plant Biologists, 2005)
Short, high-concentration peaks of the atmospheric pollutant ozone (O(3)) cause the formation of cell death lesions on the leaves of sensitive plants. Numerous similarities between the plant responses to O(3) and pathogens suggest that O(3) triggers hypersensitive response-like programmed cell death (PCD). We examined O(3) and superoxide-induced cell death in the O(3)-sensitive radical-induced cell death1 (rcd1) mutant. Dying cells in O(3)-exposed rcd1 exhibited several of the typical morphological characteristics of the hypersensitive response and PCD. Double-mutant analyses indicated a requirement for salicylic acid and the function of the cyclic nucleotide-gated ion channel AtCNGC2 in cell death. Furthermore, a requirement for ATPases, kinases, transcription, Ca(2+) flux, caspase-like proteolytic activity, and also one or more phenylmethylsulfonyl fluoride-sensitive protease activities was shown for the development of cell death lesions in rcd1. Furthermore, mitogen-activated protein kinases showed differential activation patterns in rcd1 and Columbia. Taken together, these results directly demonstrate the induction of PCD by O(3).